The Non-Suicidal Self-Injury Expectancy Questionnaire: Factor structure and initial validation - Hasking, Penelope; Boyes, M. (Wiley-Blackwell Publishing Ltd., 2017)
Background: Models of non-suicidal self-injury (NSSI) typically focus on the role of emotion regulation in NSSI, yet recent work supports a role for NSSI-related cognitions. NSSI outcome expectancies may offer important clues about who is at risk of NSSI, who is able to cease the behaviour, and who is at risk of relapse. Yet, so far, there is no reliable and valid means of assessing these cognitions. We developed, and reported on initial validation, of an NSSI Expectancy Questionnaire. Methods: A total of 49 statements reflecting possible outcomes of NSSI were administered to 496 undergraduate students. Results: Principal axis factoring revealed five factors (Affect Regulation, Negative Social Outcomes, Communication, Pain, Negative Self-Beliefs), which differentiated people with a history of NSSI from people with no NSSI history. Correlations with measures of self-efficacy, emotion regulation, and NSSI functions offer convergent and discriminant validity. Conclusions: The questionnaire appears to be a reliable and valid measure of NSSI outcome expectancies that could be a useful addition to the measurement toolkit when investigating cognitive variables related to NSSI.